1995
DOI: 10.1002/bip.360360508
|View full text |Cite
|
Sign up to set email alerts
|

Conformational study of linear alternating and mixed D‐ and L‐proline oligomers using electronic and vibrational CD and fourier transform IR

Abstract: Vibrational CD (VCD) spectra of a series of blocked linear, alternating D- and L-proline containing oligopeptides, dissolved in D2O and in CDCl3, are reported. For the Boc-LDL-Pro3 to Boc-DLDLDLDL-Pro8 oligomers, the VCD spectra in the amide I band is a positive couplet, opposite in sense to that obtained for (L-Pro)n oligomers. While this admits the possibility of their favoring a right-handed helical chain conformation, the amide I ir spectra for these DL oligomers in D2O indicate a mixed, apparently alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…The ECD spectra show negative CD at 207 and 222 nm, but have more variation in shape (and R value) for the different sequences studied and for the same molecules in different solvents. These ECD and VCD spectral shapes are distinct from spectral signatures for unordered or β‐sheet conformations and overall are fully consistent with the properties of a right‐handed helical conformation 60, 75–81. The remaining issue is whether these spectra can be used to distinguish 3 10 ‐ from α‐helices and in what way the C α ‐methyl substitution affects any of the measured spectra.…”
Section: Discussionsupporting
confidence: 60%
“…The ECD spectra show negative CD at 207 and 222 nm, but have more variation in shape (and R value) for the different sequences studied and for the same molecules in different solvents. These ECD and VCD spectral shapes are distinct from spectral signatures for unordered or β‐sheet conformations and overall are fully consistent with the properties of a right‐handed helical conformation 60, 75–81. The remaining issue is whether these spectra can be used to distinguish 3 10 ‐ from α‐helices and in what way the C α ‐methyl substitution affects any of the measured spectra.…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, CD data for peptoid 8 at varying concentrations (7–80 μ M ) in acetonitrile suggested that intermolecular interactions were not affecting the observed CD signal (Supporting Information, Figure S19). Interestingly, the CD spectra of the peptoid ribbon most closely resembled data reported for poly‐ ld ‐Pro sequences,19 which also adopt an alternating cis / trans amide backbone pattern. Beyond the dimer chain length, there were no length‐dependent changes in the CD spectral intensities.…”
Section: Sequences Purities Mass Spectrometry Data and Overall Ns1supporting
confidence: 73%
“…Two mid-infrared VCD studies of prolinecontaining cyclic peptides have been published that focused on conformation with respect to metal complexation (176) in one case and β-turn spectral features (177) in the other. Further VCD studies featuring peptides and polypeptides of proline have been carried out for oligopeptides in NH-stretching modes (178), for mixed L-and D-proline oligopeptides in combination with electronic CD (ECD) and FT-IR spectroscopy (179), and for mutarotation studies of poly-Lproline with ECD and FT-IR. Additional VOA studies have appeared for various polypeptides and their subunits.…”
Section: Applications Of Voamentioning
confidence: 99%